2010
DOI: 10.1002/abc.20032
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Students to Academic Success and Engagement on Campus

Abstract: The University of South Carolina improves struggling students' academic success and engagement on campus using a coaching framework of self‐assessment, reflection, and goal setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 1 publication
1
40
0
Order By: Relevance
“…These observations agree with the research of Robinson and Gahagan ( 2010 ) that posits coaching as a method to develop self-authorship. These observations agree with the research of Robinson and Gahagan ( 2010 ) that posits coaching as a method to develop self-authorship.…”
Section: Discussionsupporting
confidence: 91%
“…These observations agree with the research of Robinson and Gahagan ( 2010 ) that posits coaching as a method to develop self-authorship. These observations agree with the research of Robinson and Gahagan ( 2010 ) that posits coaching as a method to develop self-authorship.…”
Section: Discussionsupporting
confidence: 91%
“…However, students soon realize that college is very different from any other environment they have previously experienced (Robinson, 2010).…”
Section: Importance Of Study Habits Constructsmentioning
confidence: 98%
“…However, studies specifically related to education are beginning to emerge (Austin, 2009;Etkina et al, 2010;Murphy et al, 2005;Robinson & Gahagan, 2010;Thalluri, Kokkinn, & O'Flaherty, 2008;Vandekerckhove, 2010). Studies that explore peer coaching among students have found that it promotes active learning and relieves the teaching load (Murphy et al; Thalluri et al).…”
Section: Coachingmentioning
confidence: 99%
“…Coaching is a tool that many universities use to help students handle course content more efficiently or set goals for their education (Murphy, Mahoney, Chen, Mendoza-Diaz, & Yang, 2005;Robinson & Gahagan, 2010;Tripp, 2008). However, coaching students to improve their higher-order thinking skills online is less prevalent (Schroeder & Spannagel, 2006).…”
Section: Introductionmentioning
confidence: 99%